How to Foster PPI With Those Excluded From Public Involvement Itself? - Dinsmore, John (My University, 2018)
Background While there is encouragement of public involvement in the development of health interventions and healthcare issues, PPI seeks to go a step further with this involvement “with recognition of the need to engage citizens not only in providing feedback on health-care delivery or interventions, but in processes whereby decisions are made...” (Baxter, Clowes, Muir et al., 2016). But what happens to those citizens who find themselves socially excluded from their healthcare needs? One such group is our homeless population. This presentation, drawing upon previous research on health seeking behaviours of homeless individuals (Ní Cheallaigh, Cullivan, Sears, et al., 2017), will challenge PPI to go further in how it seeks to understand involvement. We argue that a way of achieving this is through applying experience- centred design (ECD), which gives “...people the chance to have a richer life, to include people who otherwise feel excluded, and to ensure that everybody has a chance to have their say. Especially those who often feel voiceless” (McCarthy and Wright, 2010). Methods Examples of ECD methodologies will be presented that naturally align with fostering PPI. The methods presented will attempt to equip researchers with a way to support a fluid dialogical research process, ensuring PPI across all health research contexts and not solely those of the socially included. These methods will respond to experience either in the form of digital health interventions or more service based responses. Findings & Discussion What we hope this presentation achieves is an entry point into a dialogue around how we ensure PPI, as well as responsive design of healthcare, within the homeless research context. While the presentation takes a positional stance, it seeks to provoke thought and reflection within the PPI community upon how we can achieve PPI with groups that are excluded from public involvement itself.
?International Perspectives on Evaluation of Patient & Public Involvement in Research?
PRESENTED
Newcastle, United Kingdom
Keywords: PPI; Public Involvement in Research; Patient Involvement in Research; Multimorbidity; Digital Health; Chronic Disease Management; Chronic Disease Self-Management; Ageing; Inclusive Society; Chronic Disease; Chronic Disease Management; Chronic disease self-management; Digital Health; PPI; Patient and Public Involvement in Research; Public involvement in research; multimorbidity; Age-related disability; Chronic Health Condition; Health; Social exclusion; Social participation